Price-setting dynamical duopoly with incomplete information - Ferreira, Fernanda A. (2016)
We consider a price competition in a duopoly with substitutable goods, linear and symmetric demand. There is a firm (F 1) that chooses first the price p 1 of its good; the other firm (F 2) observes p 1 and then chooses the price p 2 of its good. The conclusions of this price-setting dynamical duopoly are substantially altered by the presence of either differentiated goods or asymmetric information about rival’s production costs. In this paper, we consider asymmetric information about rival’s production costs. We do ex-ante and ex-post analyses of firms’ profits and market prices. We compare the ex-ante firms’ expected profits with the ex-post firms’ profits.